Pelatihan penerapan pembelajaran sainstivik dan penataan lingkungan untuk menfasilitasi merdeka belajar pada guru-guru KB TK Bantul - Widyastuti, Titik Mulat; Novitasari, Khikmah; Utami, Novianti Retno (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
This service is motivated by the problems faced by family planning teachers at Cluster 7 Kindergarten, Kasihan Bantul District, Yogyakarta regarding: 1). Teachers still lack understanding of the implementation of a scientific approach in learning in schools. 2). Teachers in implementing scientific learning such as observing, asking, collecting, associating and communicating information in class activities are still confused/don't understand the whole thing. This service aims to provide training and assistance in the application of scientific learning and environmental management to facilitate independent learning for early childhood. The method in this research uses: lectures, questions and answers, and supervisory actions carried out over 2 cycles. There are four stages in service activities and each cycle consists of: planning, implementation, observation and evaluation (reflection). The results of the training implementation show that PAUD teachers at KB TK Gugus 7, Kasihan Bantul District, Yogyakarta, have improved in implementing scientific learning and environmental arrangements to facilitate independent learning for early childhood children after participating in training and mentoring activities.